Research on Energy Security in the EU from a Trade Perspective: A Historical Analysis from 1991 to 2021 - Quanxiao Li; Zhouying Song (Energies, 2025)
Energy security is a global and strategic issue that is vital to national economic and social development. The conflict between Russia and Ukraine has profoundly changed the world’s energy trade structure and brought great challenges to global energy security, especially to the European Union (EU). Under this background, this study tries to construct a conceptual framework for energy security from trade and selects the EU as a case to analyze its energy security evolution at both the regional and national scales. The findings of this paper are as follows. (1) In the context of energy transition, oil and gas remain pivotal components due to their longstanding historical presence. However, they are also the most susceptible elements within the EU’s energy system. (2) The level of oil security within the EU is higher than that of natural gas. The level of oil security in member countries varies considerably, with significant geographic disparities. Aside from the exception of the Netherlands and Denmark, the majority of member countries exhibit a consistently low level of natural gas security. (3) From 1991 to 2021, the EU’s energy security pattern underwent significant changes, exhibiting a general downward trend due to the increased utilization of natural gas. In light of the aforementioned research outcomes, this paper seeks to offer policy recommendations for the enhancement of the EU’s energy security.